LITERASI DIGITAL DI SEKOLAH - Musa Musa; Aisyah Pratiwi; Safril safril (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2022)
This study aims to describe the behavior of social media consumption, find the positive and negative impacts of using social media on students at Madrasah Aliyah in Bangka Regency and find out the role and school policies on the use of social media in students. This study uses a qualitative descriptive approach with in-depth interviews with students, teachers and madrasah principals in three madrasas, namely Madrasah Aliyah Negeri 1 Bangka, Madrasah Aliyah Kemuja and Madrasah Aliyah Nurul Ihsan as informants. Based on the results of interviews, it was found that: 1) the social media consumption behavior of students has reached the technopoly stage, where the whole series of their lives have been heavily influenced by technology, especially social media, 2) social media can facilitate the learning process, facilitate interaction, add insight and support learning materials, but addiction, laziness, exposure to pornography and disturbing concentration are negative impacts of using social media, 3) prohibiting the use of smartphones in the classroom during learning.